ON THE PROBLEM OF BORROWED WORDS AS A LINGUISTIC PHENOMENON IN THE KOREAN LANGUAGE (World Bulletin of Social Sciences, 2025)
The study of the vocabulary of the Korean language has always been of great interest to linguists, since the vocabulary is replenished by borrowing from foreign languages. The study of borrowings from the English language (often called "Konglish") is one of the pressing issues in linguistic research. The problem of borrowing (Konglish) has always attracted the attention of linguists, the linguistic nature of borrowing (Konglish), the process of incorporation of foreign words and meanings into the system of the borrowing language, understanding the hidden processes of interaction between two languages - the source language and the borrowing language - have not yet received full coverage
Keywords: Konglish; Korean language; English language